2016
DOI: 10.1007/s00404-016-4010-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D status and the risk of gestational diabetes mellitus: a meta-analysis

Abstract: This meta-analysis revealed that maternal vitamin D insufficiency is associated with increased risk of gestational diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 31 publications
9
71
1
3
Order By: Relevance
“…Maternal vitamin D deficiency in early pregnancy has been associated with increased risk for GDM 62 , 63 . In the most recent meta-analysis of 20 observational studies (n = 16 515), low vitamin D levels increased the risk of gestational diabetes in 45% of participants (relative risk = 1.45; 95% confidence interval [CI]: 1.15–1.83), 62 which is consistent with previous findings 64 , 65 .…”
Section: Interventions Aiming At the Prevention Of Gestational Diabetessupporting
confidence: 85%
See 1 more Smart Citation
“…Maternal vitamin D deficiency in early pregnancy has been associated with increased risk for GDM 62 , 63 . In the most recent meta-analysis of 20 observational studies (n = 16 515), low vitamin D levels increased the risk of gestational diabetes in 45% of participants (relative risk = 1.45; 95% confidence interval [CI]: 1.15–1.83), 62 which is consistent with previous findings 64 , 65 .…”
Section: Interventions Aiming At the Prevention Of Gestational Diabetessupporting
confidence: 85%
“…In the most recent meta-analysis of 20 observational studies (n = 16 515), low vitamin D levels increased the risk of gestational diabetes in 45% of participants (relative risk = 1.45; 95% confidence interval [CI]: 1.15–1.83), 62 which is consistent with previous findings 64 , 65 . In a recent Cochrane review of vitamin D interventions including 15 RCTs, no clear difference was found for GDM, 83 but a 49% risk reduction for pre-eclampsia was observed for interventions combining vitamin D and calcium.…”
Section: Interventions Aiming At the Prevention Of Gestational Diabetesmentioning
confidence: 99%
“…Данные мета-анализов указывают на связь низких уровней 25(ОН)D во время беременности с повышен-ным риском преждевременных родов, который сни-жается при приеме препаратов витамина D [73], ге-стационного сахарного диабета [74], бактериального вагиноза, а также с низкой массой плода для данного гестационного возраста и более низкой массой ребен-ка при рождении [75,76]. При обследовании 800 бере-менных женщин, проживающих в г. Санкт-Петербург и Ленинградской области, недостаточность и дефицит витамина D встречался у 100% женщин с бесплодием, у пациенток с невынашиванием беременности дефи-цит и недостаточность витамина D наблюдался в 6 раз чаще, у беременных с преэклампсией в 5 раз чаще на-блюдался низкий уровень витамина D; при физиологи-ческой протекающей беременности недостаточность витамина D выявлена лишь у 18,5% женщин, дефицит витамина D выявлен не был [77].Результаты опубли-кованного недавно первого РКИ, в котором исследо-валось влияние приема витамина D во время бере-менности на массу костной ткани ребенка (MAVIDOS) показали, что при приеме 1000 МЕ колекальциферола во время беременности в целом не наблюдалось уве-личение массы костной ткани в сравнении с плацебо, но у родившихся в зимнее время детей было отмечено увеличение МПК почти на 10%; была также показана эффективность и безопасность приема 1000 МЕ коле-кальциферола для восполнения дефицита витамина D у беременных женщин [78].…”
Section: витамин D и репродуктивная функцияunclassified
“…Evidence from South Asian pregnant women supports a role for the combination of maternal vitamin B 12 deficiency and folate sufficiency in promoting offspring adiposity, most likely mediated through impaired maternal glucose tolerance during pregnancy [35, 36]. Meta-analysis of observational studies strongly points to a role for maternal vitamin D deficiency in GDM [37], and additional vitamin D in pregnant women with GDM has been shown to have beneficial effects on glycaemia and total and low-density lipoprotein cholesterol (LDL)-cholesterol concentrations [38]. Low zinc intake and status has also been linked with maternal glycaemia [39], and we propose that maternal glucose tolerance may be on the causal pathway linking maternal micronutrient deficiency to offspring adiposity.…”
Section: Introductionmentioning
confidence: 99%